2012
DOI: 10.1177/155892501200700103
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Impact of Plastic and Paper Shopping Bags

Abstract: This article describes the study of the eco-impact of plastic and paper bags using the life cycle impact assessment (LCIA) technique under three different options: usage and disposal criteria with the existing usage behavior to reuse and governmental policies to recycle (option1), usage and disposal criteria as per consumers’ perceptions if systems are in place (option2) and usage and disposal criteria in case of absence of recycling systems (option3). The first stage, which was the baseline for other options,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 4 publications
1
19
0
1
Order By: Relevance
“…It should also be mentioned that although paper had a smaller carbon footprint than plastic for the same weight, the packages made of paper would be heavier than the same-size plastic packages. Thus, using paper food packages instead of plastic packages would not help to reduce the EIs (Muthu et al 2012 ; Roach 2003 ), which is shown in our results.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…It should also be mentioned that although paper had a smaller carbon footprint than plastic for the same weight, the packages made of paper would be heavier than the same-size plastic packages. Thus, using paper food packages instead of plastic packages would not help to reduce the EIs (Muthu et al 2012 ; Roach 2003 ), which is shown in our results.…”
Section: Discussionmentioning
confidence: 49%
“…Thus, using paper food packages instead of Fig. 5 Average proportions of possibly reducible CO 2 equivalents caused by food delivery and food package for all the food orders, and the orders in the first-class, second-class, and third-class cities plastic packages would not help to reduce the EIs (Muthu et al 2012;Roach 2003), which is shown in our results.…”
Section: To What Extent the Eis Of Express Food Delivery Could Be Redmentioning
confidence: 68%
“…Even many other civic bodies are banning plastic use. Studies show that increase in reuse of plastic can reduce the eco-impact of plastic to a great extent [1]. In developing countries, blockage of drainage due to plastic causes calamities such as flood.…”
Section: Plastic Bagsmentioning
confidence: 99%
“…Industrial growth and anthropogenic development over the past century have continuously increased the dependency of humans on plastics. Packaging material, building and construction, transportation, medical and health, electrical and electronics, agriculture, sports and leisure products are some of the many ways in which human population utilize plastics [1][2][3][4]. Enormous amounts of waste, which is difficult to decompose, and green house gases are generated by both the production and after life remediation of plastics, which cause various kinds of health hazard problems in humans [5].…”
Section: Introductionmentioning
confidence: 99%